The effect of sunset yellow food coloring (E110) on the zebrafish (Danio rerio) embryos development - Galuh Mahardika Agustin; Dewi Puspita Sari (Universitas Pakuan, 2026)
Synthetic food coloring sunset yellow (E110) is widely used due to its color stability and low production cost; however, it may pose toxic effects during the early developmental stages of aquatic organisms. This study aimed to evaluate the embryotoxicity of sunset yellow in zebrafish (Danio rerio) embryos, determine the median lethal concentration (LC₅₀) as an indicator of acute toxicity, and analyze its effects on embryonic development, with a particular focus on somite formation. The study employed a completely randomized design (CRD) using the fish embryo toxicity test, with one control group and three treatment groups exposed to sunset yellow at 200 ppm, 400 ppm, and 800 ppm. Observed parameters included survival rate, hatching rate, heart rate, somite development, and morphological alterations in the embryo. Data were analyzed using One-Way ANOVA and Two-Way ANOVA with IBM SPSS software at a significance level of α = 0.05. The results showed that the LC50 value of Sunset yellow for zebrafish embryos was 416.67 ppm. Exposure to sunset yellow significantly decreased survival rate and hatching rate (p = 0.004 and p = 0.033, respectively) and significantly affected embryonic heart rate based on concentration and exposure duration (p < 0.001). Disruption of somite development was primarily observed during early embryogenesis, characterized by indistinct somite boundaries at higher concentrations. Additionally, concentration-dependent morphological abnormalities were observed, including shortened body length, delayed hatching, and increased body curvature. These findings suggest that Sunset yellow exhibits embryotoxic effects in zebrafish and may pose an ecological risk to aquatic organisms.